TECHNOGENIC LANDFORMS AND ASSESSMENT OF ENVIRONMENTAL RISKS AND LOSSES OF MINING ACTIVITIES IN KRYVBAS GOLDEN ORE BASIN - Korjnev, M.; Malahov, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Technogenic objects, which appeared as results of iron-ores mining and processing in the Krivoy Rog basin, and hazards, which they create for a population, are considered.